Perbandingan Moralitas Siswa antara Model Pembelajaran VCT dan STAD - Wigati Nursafitri; Erlina Rufaidah; Rahmah Dianti Putri (JEE (Jurnal Edukasi Ekobis), 2018)
This study aims to tell the difference between learning model morality on subjects IPS. The methodology that was used is research experiments with comparative approach. Population in this study are all students VIII SMP Negeri4 Pringsewu and  64 students. Test the hypothesis using analysis of data is collected that 1) there is a difference in moralitybetween students were taught using learning model of VCT and learning model of STAD, 2) Morality of students who use the model of learning VCT is better than the using learning model of STAD for students who have positive attitude on subjects IPS, 3) Morality students who use the model learning of STAD is better than the using learning model of  VCT for students who have a negative attitudeon subjects IPS,4) There is an interaction between using of those learning modelsand students’s attitude on the subjects of social students against morality. Penelitian ini bertujuan untuk mengetahui perbedaan moralitas antara penggunaan model pembelajaran yang berbeda terhadap mata pelajaran IPS. Metode yang digunakan penelitian eksperimen dengan pendekatan komparatif. Populasi siswa kelas VIII SMP Negeri 4 Pringsewu, sampel 64 siswa. Uji hipotesis menggunakan Analisis Varians Dua Jalan (ANAVA) dan T-test dua sampel independen. Hasil 1) Ada perbedaan moralitas antara siswa yang diajar menggunakan model VCT dan STAD pada mata pelajaran IPS, 2) Moralitas siswa yang pembelajarannya menggunakan VCT lebih baik dibandingkan dengan yang menggunakan STAD bagi siswa yang memiliki sikap positif terhadap mata pelajaran, 3)Moralitas siswa yang pembelajarannya menggunakan STAD lebih baik dibandingkan dengan yang menggunakan VCT bagi siswa yang memiliki sikap negatif terhadap mata pelajaran, 4) Ada interaksi antara penggunaan model pembelajaran dan sikap siswa pada mata pelajaran IPS terhadap moralitas siswa. Kata kunci: Model VCT, model STAD, moralitas, sikap belajar